GI Biopsy Crash Course - Jeremy Parfitt; David Driman (Association of American Medical Colleges, 2014)
Abstract Introduction We recognized a need at our institution for a resource to facilitate self-learning of basic gastrointestinal (GI) histology and pathology. In particular, we sought to produce an aid for GI clinical fellows participating in GI pathology biopsy rounds and preparing for their exams. We also wanted to develop a self-learning tool for other off-service/clinical residents rotating through pathology and junior-level pathology residents (within their first 2 years of residency). An interactive, web-based learning module was determined to be an ideal type of educational tool. Methods The GI Biopsy Crash Course consists of two file folders, GI Path Module and GI Crash Quiz, contained in one module, as well as an Instructor's Guide. Students work through GI Path Module, which is the teaching module, first; they then take the GI Crash Quiz after completing the teaching module. The quiz consists of 10 questions. Approximately 1-2 hours are required to work through GI Path Module and GI Crash Quiz, with most of that time spent in the teaching module. Results We have implemented the GI Biopsy Crash Course with GI clinical fellows participating in GI pathology biopsy rounds and with junior-level pathology residents going through their initial GI pathology rotations. The performance of students completing the module, although not formally evaluated, has improved noticeably. Feedback from students who have used the module has been very positive. Discussion The level of material in the GI Biopsy Crash Course is mainly introductory. We hope to create additional, higher level modules that deal with more advanced topics in GI pathology in the future.